PENGARUH PENGGUNAAN CELEBRITY ENDORSER, PERSEPSI HARGA, CITRA MEREK TERHADAP NIAT BELI ULANG SHAMPO PANTENE (Studi Pada Mahasiswa Universitas Stikubank Semarang) - Via Agillyana, 10.05.51.0081; Basiya, Robertus (Students Journal of Economic and Management, 2014)
This study aims to determine whether the celebrity endorser, price perception, and brand image influence on consumer purchase intentions over the Pantene shampoo products and analyzing the dominant factor in influencing consumer repurchase intentions Pantene shampoo in Stikubank University Semarang. The sample in this study was 100 respondents with a sampling technique that non-probability sampling (purposive sampling). Analysis of the data using qualitative and quantitative data analysis which includes Test Validity, Reliability Test, F Test, determinant coefficient, Normality Test, Regression analysis, t test. Regression analysis was carried out with the software Statistical Process Social Science (SPSS) was used to process the data. The analysis showed that, celebrity endorser positive effect on purchase intention reset, positive effect on the perception of the price of re-purchase intention, and brand image has positive influence on purchase intentions re. Hypothesis testing using t-test showed that the variables Celebrity Endorser (X1), Perceptions of Price (X2) significantly affect Repeat Purchase Intentions, whereas Brand Image (X3) does not significantly affect Repeat Purchase Intentions. While the F-test showed a significant, this means that the variable Celebrity Endorser (X1), Perceptions of Price (X2), and Brand Image (X3) jointly influence on Repurchase Intention (Y).Keywords : Celebrity Endorser, Perception Of Price, Brand Image and Repurchase Intention